Mereview Arah Undang-Undang Perbankan Syariah di Indonesia - Zuliansyah, A. (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2011)
The application of Islamic law in the activities of banking/finance Â or Â other modern economic activities is not a simple job. The study of the banking law, or sharia Â finance law to be an interesting study and challenging for the world of law in Indonesia, where the positive law (law) in the country of Indonesia is different from Â that applicable to the religious law Â (Islam). Enforcement of religious law (Islam) Â must go through a process referred to as Â the â€positivisasiâ€ Islamic law. In this case, Islamic law accepted by the state Â in Â positive laws and regulations that apply Â nationally. This paper will examine Â the law of Law no. 10 of 1998 concerning Amendment to law number 7 of 1992. Likewise, Law number 21 of 2008 has some interesting general provisions to be observed. General provisions referred to (Article 1) is a novelty and will Â provide certain implications